1997
DOI: 10.1111/1523-1747.ep12295241
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Glucocorticoid-Response Elements in Human Elastin Promoter and Demonstration of Nucleotide Sequence Specificity of the Receptor Binding

Abstract: Glucocorticoids exert their action on gene expression through activation of cytoplasmic glucocorticoid receptors (GRs) that bind to glucocorticoid response elements (GREs). The consensus GRE consists of two half sites (underlined), AGAACANNNTGTTCT. We have recently cloned the entire human elastin gene. Nucleotide sequencing of the promoter region disclosed the presence of three putative GREs with the downstream half-site sequence TGTTCC that has homology with the consensus GRE, although the upstream half site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…6A). c-Myb binds the consensus sequence NNCNTAACGGTTTT based on a binding site selection assay for yeast (7), whereas GR binds to the consensus sequence AGAACANNNTG TTCT (19). Our previous results have shown that the ϩ586 site is more important for enhancer function in Jurkat CD4 ϩ T cells than in CD4 ϩ CD8 ϩ T cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…6A). c-Myb binds the consensus sequence NNCNTAACGGTTTT based on a binding site selection assay for yeast (7), whereas GR binds to the consensus sequence AGAACANNNTG TTCT (19). Our previous results have shown that the ϩ586 site is more important for enhancer function in Jurkat CD4 ϩ T cells than in CD4 ϩ CD8 ϩ T cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids exert their effects by activating cytoplasmic glucocorticoid receptors, which result in gene expression [11]. The most well known receptor for glucocorticoids is the intracellular glucocorticoid receptor-␣ (GR␣).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Del Monaco et al, glucocorticoids were shown to induce up-regulation of human elastin promoter activity and regulate gene expression at the transcriptional level [11]. In wound healing, the extracellular matrix has an important role and elastin is an extracellular matrix protein whose secretion is enhanced by glucocorticoids [11].…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in Table 2, besides collagens, several other ECM molecules are also targeted by glucocorticoids. These include elastin (Del Monaco et al, 1997); proteoglycans decorin and biglycan (Kähä ri et al, 1995); hyaluronan (Saarni and Hopsu-Havu, 1978); noncollagenous glycoproteins, particularly fibronectin, laminin, (Stahn et al, 2007) Modulation of the expression of various types of collagen (Oikarinen et al, 1987;Russell et al, 1989;Oishi et al, 2002), elastin (Del Monaco et al, 1997), proteoglycans decorin and biglycan (Kähäri et al, 1995), HA (Saarni and Hopsu-Havu, 1978), and various noncollagenous matrix glycoproteins such as fibronectin, laminin, and tenascin (Dean et al, 1988;Simo et al, 1992;Ekblom et al, 1993); suppression of MMP synthesis and activity (DiBattista et al, 1991;Sadowski and Steinmeyer, 2001); influence on TIMP expression and activity (Sadowski and Steinmeyer, 2001) NSAIDs e.g., indomethacin, diclofenac, naproxen, and -coxibs such as celecoxib…”
Section: A Current Anti-inflammatory and Immunomodulatory Drugs Withmentioning
confidence: 99%